Determination and Assay of Some Antineoplastic Agents in Pure Form and in their Pharmaceutical Preparation - Shukla, I.C.; Yadav, O.P.; Kumar, Sanjai; Kumar, Virendra (Asian Journal of Chemistry, 2017)
In the present paper, a simple and convenient titrimetric method is reported for the determination of some antineoplastic agents i.e. chloropromazine hydrochloride, promazine hydrochloride, levamisole, fosfestrol, letrozole, and mitomycin in the pure form and in their pharmaceutical preparations i.e. relitil-25 (tablet) phenergan (tablet and injection), devormis (tablet), dicaris (tablet), levamole (tablet), vermisole (tablet), honven (tablet), lupride (tablet), progtage (tablet), almito (injection), mitocin (vial), oncicine (tablet), by using N-bromosuccinimide (NBS) reagent in acidic medium. Aliquots containing 1-5 mg of the sample were taken in 100 mL Erlenmeyer flask followed by the addition of 5 mL of (0.02 N) N-bromosuccinimide reagent and 5 mL of (4 N) CH3COOH. The reaction mixture was shaken thoroughly and allowed to react at room temperature (25-30 °C) for required reaction time (10 min). After the reaction was over 5 mL of 5 % KI was added to it, contents shaken thoroughly and allowed to stand for 1 min. The liberated iodine was titrated against 0.02 N sodium thiosulphate solution using starch indicator. A blank experiment was also run under identical conditions using all the reagents except sample. Results were calculated by the difference in the titre values of 0.02 N sodium thiosulphate for blank and actual experiment. Deviation was found within the error of ± 1 %. The value of standard deviation (SD), relative standard deviation (RSD), coefficient of variation and recovery experiments prove the method to be precise and reproducible.